Use of Wordwall-Based Islamic Education Learning Media to Increase Students' Interest in Learning at SD Negeri 1 Klieng - Fajriah, Wardatul; Husna (Jurnal Pendidikan Profesi Guru, 2025)
The development of science and technology has resulted in significant changes in various aspects of life, including in the education sector. The medium used is Wordwall, a platform that offers educational games to support interactive learning. The purpose of this study is to find out the use of Wordwall-based PAI learning media in increasing the learning interest of grade V students at SD Negeri 1 Klieng Aceh Besar, and to find out whether the use of Wordwall-based PAI learning media can increase the learning interest of grade V students at SD Negeri 1 Klieng Aceh Besar. This study uses a type of classroom action research that is carried out in two cycles. The subjects of the study were 20 students of class V. The data collection technique is carried out by observation or observation. The results of this study show that at the stage of implementation of cycles I and cycle II, students' interest in the indicator of feeling happy increased from 10% to 80%. The interest indicator increased from 15% to 80%. The attention indicator from 25% increased to 80%. And the engagement indicator increased from 15% to 85%. This proves that the use of Wordwall-based PAI learning media can increase the learning interest of grade V students at SD Negeri 1 Klieng until it reaches the success category desired by the researcher, which is 80% or reaches the stage of MSH = Increase as Expected.